Perancangan Feeds Instagram Ajakan dan Bimbingan untuk Melakukan Saat Teduh bagi Remaja Kristen - Winata, Vanni Ivana; Hagijanto, Andrian Dektisa; Malkisedek, Mendy Hosana (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
The development of digital world technology is increasingly popular today, which causes teenagers to be faced with challenges and temptations to enjoy entertainment that no longer prioritizes worship and spiritual discipline. One of the spiritual disciplines is to do devotional time to help Christian youth build positive behavior in accordance with the teachings of the Bible. However, Christian teenagers find it difficult to do devotional time regularly and often feel bored when doing devotional time. This design was made to interest Christian teenagers to do devotional time and encourage them to be able to apply it regularly. This design uses research methods with a qualitative perspective, with interview and observation data collection techniques. Collecting data on devotional time, the behavior of Christian youth in Indonesia, the use of Instagram social media, and illustration techniques as a media approach. The illustration style uses cartoon style to interest Christian youth. The media approach uses post-modernism theory by using new ways to introduce devotional time that is increasingly being forgotten in modern days. The results of the design are in the form of Instagram feeds that provide contents about introduction, invitations, and guidance to do devotional time with character illustrations. Hopefully through this design, Christian teens can start taking their time to do devotional time.